Llama Meat Nutritional Properties - G. Lebboroni; M. Antonini; C. Renieri; P. Polidori (Italian Journal of Animal Science, 2010)
The aim of this study was to determine the chemical composition of the muscle Longissimus thoracis taken from 20 llama males, reared in the Andean region, slaughtered at an age of 25 months and at a mean final body weight of 74kg. Llama meat showed a low fat (3.51%) and cholesterol content (58.16mg/100g), a good protein content (22.42%) and an ash content of 3.06%. The Warner-Bratzler shear force values determined in llama meat was 6.56 kg/cm2. This study confirmed that llama meat is healthy and nutritious, and represents a good source of proteins for Andean population.